Efforts to Improve Students' Muhadtsah Abilities Through a Communicative Approach at MA Al-Istiqamah in Learning Arabic Language on Ta'aruf Material - Faizziah Auliannisa; Ade Arip Ardiansyah; Rizzaldy Satria Wiwaha (Gunung Djati Conference Series, 2025)
This study aims to explore the efforts in improving students' muhadatsah ability through communicative approach at Madrasah Aliyah Al-Istiqamah Tanjungsiang in Arabic language learning, especially in ta'aruf material. The communicative approach is implemented through the use of dialog, group discussion, role play, and project-based activities to strengthen students' speaking ability and increase their confidence in using Arabic in real situations. This study used a qualitative approach involving classroom observation, interviews with teachers, and document analysis as data collection methods. The results show that the communicative approach is effective in creating a supportive learning environment for the development of Arabic speaking proficiency. Although faced with some challenges such as time constraints and variations in students' initial abilities, full support from school leadership and teachers' commitment became key factors in the successful implementation. The implication of this study is the importance of continuing to develop adaptive learning strategies in accordance with the dynamic and diverse context of Islamic education.